Uniform Crime Reporting Program Data: County-Level Detailed Arrest and Offense Data, United States, 2012 ([Verlag nicht ermittelbar], 2014)
This data collection contains county-level counts of arrests and offenses for Part I offenses (murder, rape, robbery, aggravated assault, burglary, larceny, auto theft, and arson) and counts of arrests for Part II offenses (forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew violations, and runaways).